AB0421 Low rates of retention of biologic dmard monotherapy in patients with rheumatoid arthritisin real life settings. (12th June 2018) - Lazarini, A.; Thomas, K.; Kaltsonoudis, E.; Drosos, A.; Tsatsani, P.; Gazi, S.; Pantazi, L.; Boki, K.A.; Katsimbri, P.; Boumpas, D.; Fragkiadaki, K.; Tektonidou, M.; et al.
Abstract : Background: A number of cross-sectional studies have shown that approximately one quarter of rheumatoid arthritis (RA) patients are being treated with biologic disease modifying anti-rheumatic drugs (bDMARDs) as monotherapy. Data regarding the retention of bDMARD monotherapy in real-life settings are limited. Objectives: To study the survival rate of bDMARD monotherapy in RA patients in daily clinical practice. Methods: Multicenter (11 hospital, 3 private office practices), prospective, RA epidemiological study in Greece. At baseline and after one year of follow-up, demographics, disease characteristics, treatments, co-morbidities and serious events (serious infections, cardiovascular events, neoplasms, osteoporotic fractures) were collected via a web-based platform. Results: 1.323 RA patients with paired evaluations one year apart (mean interval: 13.2±3.7 months) were included. Among 611 bDMARD treated patients, 155 patients (25%) were on bDMARD monotherapy (women: 87%, mean age: 60.4 years, mean disease duration: 15 years, RF and/or anti-CCP positive: 66%, TNFi therapy: 57%). The majority had been previously on and had discontinued their csDMARDs (90%). During follow-up, 15% (n=24) discontinued their bDMARD; most of them stayed off any type of therapy (83%) while the rest continued with synthetic DMARD (csDMARD) monotherapy (17%). From the remaining 131 patients, 96 (73%) remained on bDMARD monotherapy (85%, n=82 on the same biologic) while in 27% (n=35) a csDMARD was added. Serious events occurred in 7.7% of patients (n=12). Overall, at the end of 1st year, approximately half of patients (53%, n=82) remained on their initial bDMARD monotherapy. Factors associated with continuation of the same bDMARD by multivariate analysis were a low HAQ score (OR=0.48, 95% C.I.=0.23–0.99, p=0.047) and corticosteroid use (OR=2.2, 95% C.I.=1.02–5.1, p=0.044) at baseline as well as the absence of a serious event during the 1st year of follow-up (OR=0.14, 95% C.I.=0.016–1.3, p=0.094). Conclusions: In real life settings, only half of patients who are on bDMARD monotherapy continue the same agent one year later. Low HAQ score, corticosteroid use and absence of a serious event during therapy predicted bDMARD monotherapy survival. Acknowledgements: Supported by grants from the Greek Rheumatology Society and Professional Association of Rheumatologists. Disclosure of Interest: None declared